Analisis Partisipasi Orang Kolok dalam Pengembangan Desa Wisata di Desa Bengkala, Buleleng, Bali - Legawa, I Gede Andi (Sunari Penjor : Journal of Anthropology; Vol 8 No 2 (2024): Volume 8. No. 2. September 2024DO - 10.24843/SP.2024.v8.i02.p05, 2024)
The phenomenon of tourist village has indeed become a concern in recent years. One of the unique villages in Buleleng Regency and even in Indonesia is the tourist village of Bengkala village. This village features a disability group, the kolok group as main icon through the kolok janger dance. This is what drive this research by asking question: 1) how the participation of kolok people in the development of tourism village in Bengkala village, and 2) what is the impact of involvement of kolok people on the development of tourism village in Bengkala village. To explain and understand this, several perspective and approaches to participation are used. The research method used is a qualitative research method. The location chosen for this study is located in Bengkala village, Kubutambahan district, Buleleng regency, Bali. The data analysis, the author used descriptive qualitative analysis to be able to describe, interpret, and describe data collected systematically. They belong to the passive participatory tourism group. The group is more directed in tourism activities (as dancer) and is almost not involved in the process of decision making to develop a tourism village in Bengkala.